Chapter Tidal Turbine Generators - Polinder, Henk (InTechOpen, 2020)
Recently, tidal stream turbines have become a preferable mode of harvesting tidal energy. The main issue for low utilization of tidal energy is the high levelized cost of energy (LCoE) from tidal stream turbines. A major reason for this is the high operation and maintenance costs for submerged installations. A possible way of minimizing the LCoE and improving the availability is to use a flooded (or a wetgap) generator rather than a conventional airgap generator. Inside flooded generators, the gap between the stator and rotor is filled with the seawater. This architecture has the potential to improve cooling and reduce reliance on ancillary systems (e.g., bilge system), thereby improving reliability. The chapter begins with a brief description of the generator systems used in current tidal stream turbines. The focus of the chapter is, however, to give a basic insight into the design aspects of the flooded generators, and compares it with the currently used sealed airgap generators in tidal turbine systems.